New PAR1 Agonist Peptide Demonstrates Protective Action in a Mouse Model of Photothrombosis-Induced Brain Ischemia - Galkov, Maksim; Kiseleva, Ekaterina; Gulyaev, Mikhail; Sidorova, Maria; Gorbacheva, Liubov (Frontiers in Neuroscience, 2020)
Protease-activated receptors (PARs) are involved not only in hemostasis, but also in the development of ischemic brain injury. In the present work, we examined in vivo effects of a new peptide (AP9) composing Asn47-Phen55 of PAR1 "tethered ligand" generated by activated protein C. We chose a mouse model of photothrombosis-induced (PT-induced) ischemia to assess AP9 effects in vivo. To reveal the molecular mechanism of AP9 action, mice lacking β-arrestin-2 were used. AP9 was injected intravenously once 10 min before PT at doses of 0.2, 2, or 20 mg/kg, or twice, i.e. 10 min before and 1 h after PT at a dose of 20 mg/kg. Lesion volume was measured by magnetic resonance imaging and staining of brain sections with tetrazolium salt. A neurologic deficit was estimated using the cylinder and the grid-walk tests. Blood-brain barrier disruption was assessed by Evans blue dye extraction. Eosin and hematoxylin and immunohistochemical staining were applied to evaluate the number of undamaged neurons and activated glial cells in the penumbra. A single administration of AP9 (20 mg/kg), as well as its two injections (20 mg/kg) decreased brain lesion volume. A double administration of AP9 also reduced blood-brain barrier disruption and neurological deficit in mice. We did not observe the protective effect of AP9 in mice lacking β-arrestin-2 after PT. Thus, we demonstrated for the first time protective properties of PAR1 agonist peptide, AP9, in vivo. β-Arrestin-2 was required for the protective action of AP9 in PT-induced brain ischemia.